2015
DOI: 10.1021/ja512552g
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Responsive Metal–Organic Framework

Abstract: Two-photon processing presents a facile means to tailor the properties of materials in three-dimensions. A two-photon responsive metal-organic framework (MOF) has been realized through the incorporation of a photoactive linker into a MOF via a multivariate strategy. The resulting MOF exhibits a significant one-photon and two-photon excited fluorescence change in response to UV light and infrared femtosecond laser, enabling spatial modulation of the fluorescence property of the MOF. It thus demonstrates the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
124
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 191 publications
(128 citation statements)
references
References 47 publications
4
124
0
Order By: Relevance
“…Several studies of asymmetric azobenzenes have suggested that the decrease in relative intensity of peaks between 1400 and 1550 cm À1 is indicative of an isomerisation process. [51,52] Crystal Structure and Thermophysical Properties of [Zn 4 (tbazip) 3 (Fig. S3, Supplementary Material).…”
Section: Trans-cis Isomerisation Of Discrete Tbazipmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies of asymmetric azobenzenes have suggested that the decrease in relative intensity of peaks between 1400 and 1550 cm À1 is indicative of an isomerisation process. [51,52] Crystal Structure and Thermophysical Properties of [Zn 4 (tbazip) 3 (Fig. S3, Supplementary Material).…”
Section: Trans-cis Isomerisation Of Discrete Tbazipmentioning
confidence: 99%
“…The spaces occupied by these solvent molecules are connected to neighbouring solvent spaces to form channels along the a-axis. The observed porosity in [Zn 4 (tbazip) 3 attributable to the partial retention of these channels upon evacuation of the solvent molecules. PXRD analysis was employed to confirm the bulk purity of [Zn 4 (tbazip) 3 (bpe) 2 (OH) 2 ]ÁbpeÁ2H 2 O (Fig.…”
Section: Trans-cis Isomerisation Of Discrete Tbazipmentioning
confidence: 99%
See 3 more Smart Citations